Prolonged Opioid Usage After Surgically Treated Pelvic Fracture in Working Aged Patients: Prevalence, Demographics, and Multivariable Prediction Model - Ekman, Elina; Liukkonen, Rasmus; Reito, Aleksi (Wiley, 2026)
Background: Pelvic fracture (PF) is a serious injury that can lead to prolonged opioid use. We examined opioid use after surgical treatment of PF in a working-age population in Finland and identified predictors of prolonged opioid use. Methods: Using nationwide registries, we identified all Finnish inhabitants aged 18 to 65 years undergoing PF surgery between 2015 and 2021 (n = 233). These patients' demographic data, depression, trauma mechanisms, opioid purchases, and socioeconomic status were retrieved. The primary outcome was the prolonged opioid usage, defined as having more than one opioid prescription filled after the first three postoperative months. Logistic regression and Poisson zero-inflated (ZIP) regression analyses were performed to examine the predictors of prolonged opioid usage. The results are reported as adjusted odds ratios (aORs) or adjusted incidence rate ratios (aIRRs) with 95% confidence intervals. Results: At 3–12 months and 6–12 months postoperatively, 40.3% and 33.0% of patients used opioids (at least one prescription), respectively. Preoperative opioid use (3–12 months: aOR 6.59, 95% CI [2.23, 24.38]; ZIP-aOR 0.16, 95% CI [0.05, 0.50]; aIRR 2.19, 95% CI [1.81, 2.64]) was the single most important predictor of postoperative opioid use. Depression (aOR 2.08, 95% CI [1.09, 4.02]; ZIP-aOR 0.48, 95% CI [0.25, 0.92]) showed modest effect at 3–12 months. Predictive performance of the regression for postoperative opioid use was low based on R2 and AUC values. Conclusion: Prolonged opioid use was common. The predictive ability of the regression models for prolonged opioid use was modest and preoperative opioid use was the most important predictor. Significance Statement: In this nationwide registry study, we found that prolonged opioid use after surgically treated PF in Finland's working-age population is common as 40.3% of the patients used opioids still over 3 months after the surgery. Preoperative opioid use and depression predicted prolonged opioid use. Also, preoperative opioid use, depression, younger age, PF operation during winter and falling or jumping from height were associated with increased opioid prescription volume. Opioids should not be prescribed after 3 months of the index surgery as one in seven PF patients became opioid dependent.